1997
DOI: 10.1103/physrevlett.78.2775
|View full text |Cite
|
Sign up to set email alerts
|

Selective Study of Fe Atoms at the Interfaces of an Fe/Ir(100) Superlattice by means of Diffraction Anomalous Fine Structure

Abstract: Studies of superlattices are important in order to synthesize 3D metals in a new crystalline structure which may exhibit exotic magnetic properties. The challenge is to relate these properties to the details of the chemical gradient and the local strain. We report the use of diffraction anomalous fine structure (DAFS) spectroscopy and a crystallographic analysis of the DAFS data to separate the x-ray-absorption fine structure (XAFS)-like information about Fe atoms located at different crystallographic sites of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 13 publications
(10 reference statements)
0
31
0
Order By: Relevance
“…DAFS methods have evolved towards applications dedicated to materials sciences, such as element selective observations of interfaces [61]. Similarly, it has been shown that DAFS spectroscopy combined with MAD can be exploited to obtain structural information of nanostructures, in particular nano-islands or nanowires grown on Si (001) [62].…”
Section: Characterising Materialsmentioning
confidence: 99%
“…DAFS methods have evolved towards applications dedicated to materials sciences, such as element selective observations of interfaces [61]. Similarly, it has been shown that DAFS spectroscopy combined with MAD can be exploited to obtain structural information of nanostructures, in particular nano-islands or nanowires grown on Si (001) [62].…”
Section: Characterising Materialsmentioning
confidence: 99%
“…Because of this, DAFS may distinguish the valence and local environment of atoms of the same atomic number located on different crystallographic sites. This has been used, for example, to recover the Fe scattering anomalous terms of the tetrahedral and octahedral sites in magnetite [Pickering et al, 1993a], the local environment of Cu1 and Cu2 sites in the superconductor Y Ba 2 Cu 3 O 7 [Cross et al, 1997, Cross et al, 1998b, and the interface structure of an Ir/Fe superlattice [Renevier et al, 1997]. In the special case of magnetite, there exist Bragg reflections strictly sensitive either to the octahedral or tetrahedral sites and without contribution from the other site.…”
Section: Selectivitymentioning
confidence: 99%
“…However the EDAFS technique (combined or not with DANES) seem to be far more powerful when applied to thin films, to determine the local environment of Cu sites in the superconductor YBa 2 Cu 3 O 7 [45,46] or to investigate the interface structure of an Ir/Fe superlattice [47].…”
Section: Edafs For Site Selective Studiesmentioning
confidence: 99%